Integritas Intelektual Menurut Al-Qur’an - Mahfudzi Mahfudzi (Fakultas Ushuluddin dan Dakwah Institut Ilmu Al-Qur'an (IIQ) Jakarta, Indonesia, 2019)
Intellectual Integrity is a combination of literacy, competence, and character. Combining literacy, competence, and character as the fruit of the unification of the head, hand and heart work system through the education process. The conclusion of this research is disagreeing with V. Henry Douglas who states that arrogant actions can only be prevented by literacy and competence, without involving elements of character. Furthermore, this research supports. Residents P Gregg and Nikhila Mahadevan Anthony Gidden's, Paul. F Kniter. Thomas Metjinger. Nasih A. Ulwan. Mohammad Kamal Hasan. Alfred binet and Theodore Simon,. William H. Calvin ,. Al-Mawardi. which states that moral character and performance character contribute greatly to creating unity and are able to prevent various forms of acts of violence and multi-sectoral conflict. The research used is library research and descriptive qualitative analysis with a philosophical approach consisting of linguistic analysis and concept analysis. In this case the concept studied is the concept of Intellectual Integrity according to the quran. Intellectual Integrity is part of the study of ethical philosophy (berten 1993, algermond.black 1993) which is then associated with education. While the main source of this dissertation is the tafsir books of the Qur'an and hadith.